2006
DOI: 10.4049/jimmunol.177.9.5791
|View full text |Cite
|
Sign up to set email alerts
|

Harboring of Particulate Allergens within Secretory Compartments by Mast Cells following IgE/FcεRI-Lipid Raft-Mediated Phagocytosis

Abstract: Although much is known regarding the exocytic responses of mast cells following allergen/IgE-mediated activation, little is currently known of the fate of the activating allergens, many of which are particles. We have found that IgE-bound particulate allergens were phagocytosed by activated mast cells in a lipid raft-dependent manner. The nascent allergen-containing phagosomes were found to transform into granule compartments by acquiring VAMP7 and serotonin and exhibited the capacity to empty their contents u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…These findings, in concert with recent observations that IgE-sensitized MCs retain naturally particulate allergens without degradation for extended periods of time (26), suggest a scenario in which pulmonary MCs mediate sustained signaling for extended periods of time after exposure to pAgs. This model may be supported by observations in asthmatic patients, in which MCs exhibit a chronically activated phenotype, even after exposure of the patient to the offending allergen has been eliminated (15).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…These findings, in concert with recent observations that IgE-sensitized MCs retain naturally particulate allergens without degradation for extended periods of time (26), suggest a scenario in which pulmonary MCs mediate sustained signaling for extended periods of time after exposure to pAgs. This model may be supported by observations in asthmatic patients, in which MCs exhibit a chronically activated phenotype, even after exposure of the patient to the offending allergen has been eliminated (15).…”
Section: Discussionsupporting
confidence: 62%
“…Our previous study revealed that the FcεRI-mediated phagocytosis of pollen into MCs is lipid raft dependent (26). Lipid rafts are specialized membrane domains that are dynamic assemblies of proteins, lipids and signaling substrates (27)(28)(29).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The colorimetric hexosaminidase release assay was employed as described previously (33). Briefly, BMMCs equilibrated with Tyroid buffer were mixed with human IgE or anti-hFcεRI antibody:anti-mouse IgG antibody complexes in a 96 well plate.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that the injected human IgE had been pre-tested and confirmed for the absence of aggregates that can potentially activate hFcεRI-expressing cells by crosslinking hFcεRI. Briefly, we added the human IgE preparation to mast cells cultured from FCER1A-Tg mouse bone marrow and measured degranulation of these cells by a hexosaminidase release assay (33). The addition of up to 10 μg/ml of IgE to the cells did not cause any release of hexosaminidase above the level of spontaneous release (Supplemental Figure 8).…”
Section: Fcεri Is Specifically Localized In Endolysosomes Of Dcs and mentioning
confidence: 99%